1978
DOI: 10.1161/01.cir.58.3.460
|View full text |Cite
|
Sign up to set email alerts
|

Aortic input impedance in heart failure.

Abstract: SUMMARY The input impedance of the systemic circulation was calculated from recordings of pulsatile pressure and flow in the ascending aorta of 20 patients. Ten patients had clinical and hemodynamic evidence of heart failure. The other 10 subjects had no clinical evidence of heart failure and were used as a control group. In the heart failure patients, both input resistance and characteristic impedance (index of aortic distensibility) were significantly increased compared to pressureand age-matched control sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
66
1
6

Year Published

1979
1979
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(79 citation statements)
references
References 19 publications
6
66
1
6
Order By: Relevance
“…10 Although the normal mean characteristic impedance in that study was similar to our normal control group, mean ZL in their patients with heart failure was significantly elevated at 131 + 27 dyne-sec-cm -. In a more recent report, mean aortic characteristic impedance in subjects with heart failure and cardiomyopathy was quite similar to our mean data."…”
Section: Cm)supporting
confidence: 59%
See 2 more Smart Citations
“…10 Although the normal mean characteristic impedance in that study was similar to our normal control group, mean ZL in their patients with heart failure was significantly elevated at 131 + 27 dyne-sec-cm -. In a more recent report, mean aortic characteristic impedance in subjects with heart failure and cardiomyopathy was quite similar to our mean data."…”
Section: Cm)supporting
confidence: 59%
“…10 The possibility of increased arterial wall sodium content with a secondary decrease in distensibility raises the intriguing possibility of altering arterial elastic properties in patients with heart failure with diuretic therapy. All of our patients with heart failure were studied after appropriate medical therapy and were in a clinically stable condition at the time of catheterization.…”
Section: Cm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding proximal arterial stiffness, conflicting results have been published. Using characteristic impedance as a direct marker of arterial stiffness, Mitchell et al 29 and Pepine et al 30 found an increase in proximal arterial stiffness, whereas Merillon et al 31 and Kromer et al 32 did not. These conflicting results are probably partly due to methodological differences, but no data are available for patients with very low EF.…”
Section: Discussionmentioning
confidence: 99%
“…'-' In comparisons of changing load under different circumstances, vascular impedance is usually expressed as characteristic impedance.3 5 7-9 Characteristic impedance has been used also as an index of arterial distensibility and this (when expressed in appropriate units) has been shown to change in different disease conditions with different drugs and with increasing age. , [9][10][11][12][13][14][15] Characteristic impedance of an arterial segment is directly related to regional arterial pulse wave velocity (PWV). 0 Regional PWV can be determined from the time delay between the foot of pulse waves recorded in proximal and distal sites and the distance between recording sites.…”
mentioning
confidence: 99%